Development of an IoT-Based Smart Hydroponic Monitoring System as a Modern Agricultural Solution in Remote Areas - Laia, Firdaus; Laia, Finis Hermanto; Telaumbanua, Setia Murni; Sitorus, Halasan Pardamean; Hondro, Fernando Jofannikus (Institute of Computer Science (IOCS), 2025)
This research was motivated by the low agricultural productivity on Nias Island caused by limited land availability, inadequate infrastructure, restricted access to modern technology, and highly variable climatic conditions. This study aims to develop an Internet of Things (IoT)-based smart hydroponic monitoring system capable of automatically monitoring key parameters such as temperature, pH, water quality, and nutrient levels in real time, integrated with mobile applications and cloud platforms for remote accessibility. The research methodology consists of needs analysis, system design, prototype implementation, testing, and performance evaluation. The test results demonstrate that the developed prototype operates effectively, with sensor accuracy showing an average error of 3.74% for TDS, 1.28% for pH, and 0.91% for temperature measurements, while actuator testing confirmed 100% correct system response to nutrient and pH control scenarios. The system also maintained stable data transmission to mobile and cloud platforms without significant latency. These findings indicate that the proposed IoT-based monitoring system can significantly improve the efficiency and productivity of hydroponic agriculture, particularly in resource-limited regions such as Nias Island. The study provides empirical evidence of the system’s performance, reinforcing its potential as a practical solution for modernizing agriculture in remote areas.